Fused Double Supernumerary Premolars of the Mandible: A Rare Case - Ali Azhar Dawasaz; Syed Sadatullah; Syed Kamran Bokhari (Hindawi Limited, 2012)
The incidence of nonsyndromic supernumerary premolars is rare. Supernumerary premolars are likely to undergo pathological changes. The most commonly encountered complications with these teeth are dentigerous cyst and root resorption of the adjacent tooth. This paper is about impacted double fused supernumerary premolars in the right mandiblular body associated with an impacted first premolar in a 17-year-old male. Under local anesthesia, the supernumerary premolars and the impacted permanent first premolar were surgically removed. Early diagnosis followed by an appropriate treatment at the right time will result in favorable prognosis in such cases.